2011
DOI: 10.1111/j.1365-2265.2010.03919.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of PHEX, FGF23 and DMP1 in a cohort of patients with hypophosphatemic rickets

Abstract: Summary Background X-linked hypophosphatemic rickets, autosomal dominant hypophosphatemic rickets and autosomal recessive hypophosphatemic rickets make up a group of renal phosphate wasting disorders with common clinical and biochemical characteristics. These three types of rickets are related to mutations in PHEX, FGF23 and DMP1, respectively. Objective The objective of the study was to evaluate the frequency of mutations that occur in these three genes associated with hypophosphatemic rickets. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 43 publications
2
48
1
3
Order By: Relevance
“…The overall median detection rate of gene mutations reported in previous studies comprising 15 or more HR probands was 66% (range 43-100%), 20,[27][28][29][30][31][32][37][38][39][40][41] in familial probands 66% (44-100%), and in sporadic probands the detection rate was 50% (29-100%). 20,[27][28][29][30]32,37,38 In our study, the MLPA analysis added three PHEX mutations not identified by PCR, dHPLC or sequencing, thus increasing our overall detection rate from 78 to 88%, in familial probands from 67 to 83% and in sporadic probands from 83 to 92%. Our high detection rate of gene mutations, especially among the sporadic patients, may also be due to the robust inclusion/ exclusion criteria of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall median detection rate of gene mutations reported in previous studies comprising 15 or more HR probands was 66% (range 43-100%), 20,[27][28][29][30][31][32][37][38][39][40][41] in familial probands 66% (44-100%), and in sporadic probands the detection rate was 50% (29-100%). 20,[27][28][29][30]32,37,38 In our study, the MLPA analysis added three PHEX mutations not identified by PCR, dHPLC or sequencing, thus increasing our overall detection rate from 78 to 88%, in familial probands from 67 to 83% and in sporadic probands from 83 to 92%. Our high detection rate of gene mutations, especially among the sporadic patients, may also be due to the robust inclusion/ exclusion criteria of this study.…”
Section: Discussionmentioning
confidence: 99%
“…We determined a mutation to be disease causing: (1) when the mutation was previously described in the PHEXdb (accessed April, 2012) or characterised in publications, but not yet appearing in the PHEXdb; [20][21][22][23] (2) when the mutation identified was present in all family members with clinically and biochemically verified HR, but not in any of the asymptomatic family members; and/or (3) when the mutation type was predicted to cause a nonfunctional protein as frameshift, deletion, duplication, nonsense or abnormal splicing. Missense mutations were initially tested by the prediction software PolyPhen ('polymorphism phenotyping' , http://genetics.bwh.harvard.edu/pph/) and SIFT ('sorting intolerant from tolerant' , http://sift.jcvi.org/) to predict the impact of missense mutations on protein structure and function based on sequence alignments.…”
Section: Genetic Analysismentioning
confidence: 99%
“…По данным зарубежных исследований [15][16][17][18][19][20], в больших когортах пациентов с ГФР поломки гена PHEX определяются в 50-80% случаев. С. Gaucher и соавт.…”
Section: Discussionunclassified
“…В литературе имеется описание пациентов с со-четанием дефектов гена PHEX с мутациями в генах DMP1, FGF23 [19]. Среди пациентов нашей когорты только у одного выявлена гемизиготная мутация в гене PHEX (p.I174fs) и гетерозиготная мутация в гене DMP1 (р.Q159K), которая была ранее описана [19].…”
Section: Discussionunclassified
See 1 more Smart Citation